Characteristics of bullying in Belgrade high schools - Adrijana (Sociološki pregled, 2024)
The paper presents the results of the study on the prevalence of bullying and its relationship with student’s sex and age, distribution of student roles, as well as characteristics of a bully such as sex, age and number. The survey data were obtained from 1,526 high school students in grades 2 through 4, from 19 Belgrade high schools. The findings of the study show that during the 2019/2020 school year slightly more than one third of students were involved in bullying. When it comes to bullying victimization, Belgrade high schools are slightly below the world average. Other characteristics generally do not differ from those found in previous research, and its main peculiarity is the fact that older students were more likely to experience bullying victimization, whereas no age-related differences were found when it comes to bullying perpetration.